2018
DOI: 10.1016/j.soard.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in the adverse outcomes in weight loss surgeries

Abstract: DVT and sepsis are more likely to occur in colder seasons compared with the summer season, although the crude rates of these adverse events were low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
2
Order By: Relevance
“…The in uence of operative season on patient outcomes has recent attracted research interest. Several studies have demonstrated that patients undergoing surgery during the winter have increased morbidity and mortality [5,6,8,27]. It has been hypothesized that weather conditions could follow a seasonal pattern in uenced by temperature, sun exposure or viral infections; however, we found no seasonal pattern in CRC surgery outcomes, as the clusters of months followed a non-consecutive distribution.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The in uence of operative season on patient outcomes has recent attracted research interest. Several studies have demonstrated that patients undergoing surgery during the winter have increased morbidity and mortality [5,6,8,27]. It has been hypothesized that weather conditions could follow a seasonal pattern in uenced by temperature, sun exposure or viral infections; however, we found no seasonal pattern in CRC surgery outcomes, as the clusters of months followed a non-consecutive distribution.…”
Section: Discussioncontrasting
confidence: 65%
“…Likewise, a cyclical pattern has been suggested for shortterm outcomes of surgery [24][25][26]. It has been reported that postoperative complications in pancreatic or bariatric surgery may present variable incidence, with peak periods of worse outcomes that could show a monthly cyclical pattern [27,28]. However, these ndings have not been reported for CRC surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgeries in that study were different, they were all thoracic surgeries, and the results were similar to our study. A study on postoperative complications of bariatric surgery in the United States reported that although adverse events, such as deep vein thrombosis and sepsis, were rare, they were more likely to occur in the cold season than in summer (15). We found no significant seasonal difference in these complications.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies on the seasonal chronology of surgical complications regardless of the influence on 25(OH)D are limited. One preliminary study explored the seasonality pattern of perioperative adverse outcomes after bariatric surgery, denoting higher incidence of deep venous thrombosis and sepsis in colder seasons, and proposing the significance of seasonality ( 41 ). It is shown that the percentage of weight lost in the three months after bariatric surgery is higher during the summer months (July–November) ( 42 ).…”
Section: Discussionmentioning
confidence: 99%